Development of Seribu Rumah Gadang Village as a Tourism Destination - Gisky Andria Putra (Jurnal Abdimas Cendekiawan Indonesia, 2024)
The Seribu Rumah Gadang village holds immense potential as a tourist destination awaiting development. The primary objective is to foster the continuous progress and growth of the tourism sector in West Sumatra, consequently bolstering the economic landscape. This research adopts a descriptive methodology with a qualitative approach. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is employed as the data analysis technique. The findings highlight the necessity of formulating development strategies for the village of a thousand "rumah gadang" using SWOT analysis. This approach elucidates the strengths, weaknesses, opportunities, and threats inherent in development, facilitating the formulation of an optimal development strategy. Crafting the right strategy for developing the village of a thousand "rumah gadang" as a tourist attraction is paramount. Leveraging the village's strengths to optimize tourism opportunities is identified as an effective approach. By synergizing natural beauty, cultural uniqueness, environmental sustainability, culinary delights (rendang), favorable environmental conditions, accessible infrastructure, hospitable community attitudes, and security measures provided by authorities, the village of a thousand "rumah gadang" stands poised to emerge as a premier tourist destination, appealing to both domestic and international visitors.